Frequency and Risk Factors Associated with Postoperative Sore Throat (POST) in Adults Undergoing General Anesthesia during ENT and Eye Surgery: A Cross-Sectional Study: POST in Adults Undergoing General Anesthesia During ENT and Eye Surgery - Khan, Asad; Ullah, Inam; Khawaja, Aroob Zaki; Bary, Abdul; Ullah, Taimoor Riaz; Shahbaz, Sumbal; Ali, Niaz (Pakistan Journal of Health Sciences, 2025)
Postoperative Sore Throat and hoarseness are two common complications after intubation during general Anesthesia. It is crucial to understand the frequency and associated risk factors of POST to improve patients’ outcomes and reduce its incidence in patients of ENT and eye surgeries undergoing General Anesthesia (GA). Objectives: To emphasize the frequency and risk factors of POST after endotracheal intubation in patients undergoing GA for elective ear, nose, throat (ENT) and eye surgeries. Methods: A DHQ Hospital hosted this cross-sectional study from August 2024 to October 2024. The number of participants was 215. A consecutive non-probability sampling technique was used for patient selection. The ASA tool was used to assess the health status of patients undergoing GA. All participants were observed perioperatively, including for 10 minutes in the Post Anesthetic Care Unit (PACU). This was not a blinded study. Results: In this study, female subjects comprised 62.8% of the total sample. Complications included sore throat in 102 patients (47.4%) and hoarseness in 25 (24.2%). After the surgeries lasting for 31-60 minutes (51 cases, p=0.01) and in throat surgeries (89 cases, p=0.006), the sore throat was more common. Conclusions: Sore throat and Hoarseness are two common complications reported postoperatively with high frequency. The problem may arise more frequently during long surgical procedures; other factors may include the type of surgery, use of an NG tube, and large diameter ETT size. Knowing these hazards makes it clear that the best airway management techniques are required to reduce patient discomfort and enhance recovery.